Accurate and time‐saving, two‐step intracavernosal injection procedure to diagnose psychological erectile dysfunction. (21st March 2022) - Santi, Daniele; Spaggiari, Giorgia; Simoni, Manuela; Granata, Antonio R. M.
Abstract: Background: The recognition of the erectile dysfunction pathogenesis is essential to identify the appropriate erectile dysfunction management. As vascular erectile dysfunction could be a manifestation of a systemic arterial damage, the watershed in the erectile dysfunction diagnostic framework is the discrimination between psychological erectile dysfunction and vascular erectile dysfunction. However, reliable tools to directly diagnose psychological erectile dysfunction are currently lacking. Objective: To identify which parameters could predict psychological erectile dysfunction. Moreover, we suggest a new intracavernosal injection procedure to optimize the erectile dysfunction diagnostic workup. Materials and methods: A retrospective, real‐world analysis was carried out including all men who underwent intracavernosal injection procedure at the Modena Andrology Unit from 2018 to 2021. A first intracavernosal injection procedure with 5 µg of prostaglandin E‐1 (PGE‐1) was performed. In the absence of a full drug‐induced erection (immediate or delayed), an echo‐color Doppler penile evaluation after administration of PGE‐1 10 µg was conducted, measuring intracavernosal blood flows, to document a possible vascular etiology. Hormonal evaluations were performed. Results: Out of 179 enrolled patients, 70.4% showed psychological erectile dysfunction, 21.7% vascular erectile dysfunction, and 7.8% hormonal genesis. Multinomial logistic regression analysis identified absence of cardiovascular disease ( p = 0.017), presence of spontaneous morning erections ( p = 0.018), and normal penile erections with masturbation ( p = 0.035) as predictors of psychological erectile dysfunction. Clinically, normal intracavernosal injection test response was detected in 86 patients and abnormal response in 93 subjects. Among the latter, 54 patients experienced a delayed response. The combination of intracavernosal injection test with late penile erections evaluation was able to diagnose psychological erectile dysfunction (sensitivity 97%, specificity 100%), avoiding unnecessary retesting. Discussion: We propose a two‐step intracavernosal injection procedure that allows to recognize psychological erectile dysfunction with a high sensitivity/specificity, saving costs and time, and limiting adverse events. Moreover, the presence of spontaneous morning erections and valid penile erections after masturbation could guide the diagnostic workup, indirectly identifying those patients deserving of a deeper evaluation of vascular health.